El equilibrio químico desde un ambiente de aprendizaje por investigación: una propuesta para el desarrollo de habilidades de pensamiento científico - Franco Moreno, Ricardo Andrés; González Acosta, Catherin Viviana (Revista Científica, 2016)
Starting from the premise that chemical equilibrium is a structuring concept of the conceptual and methodological basis of chemistry, in whose learning research in didactics of this discipline reports multiple difficulties, complexities and shortcomings, which must be understood as an opportunity and A challenge to improve the teaching of scientific concepts in the initial training of science teachers, in this article a research proposal is communicated, with a view to promoting the development of scientific thinking skills in future Natural Sciences graduates through the formulation, development and evaluation of an integrated environment for learning the chemical equilibrium by oriented research, linking priority research lines in didactics of experimental sciences.